A Paleomagnetic Analysis of the Deformation and Hydrothermal Alteration in the Killarney Igneous Complex, Ontario - Wiacek, Andrew (My University, 1989)
The Killarney Igneous Complex lies along the Grenville Front, forming a wedge between the Grenville and Southern Provinces of the Canadian Shield. The complex consists of a granitic pluton and associated felsic volcanic rocks that have been subjected to both mid-Proterozoic and Grenvillian tectonism. This study sought paleomagnetic confirmation of pre-Grenville deformation by carrying out AF and thermal demagnetization experiments on 226 samples representing both the massive and foliated parts of the complex. This was accompanied by an analysis of polished thin-sections to attempt to determine a paragenesis for the remanence carrying minerals.
Sixty-four specimens of foliated and veined, hematiteenriched porphyry carry a stable southwesterly magnetization (Declination= 242.4°, Inclination= -26.4°, K = 17.5, A95 = 11.2°) or its antipole. The paleomagnetic pole implied by this magnetization (Longitude= 19.3°E, Latitude= 29.1°, dp = 9.6°, dm = 10.9°) is consistent with an age of somewhat less than 1100 Ma. This magnetization is a CRM that was acquired during the hydrothermal alteration of the porphyry. As a consistent magnetization is carried by highly sheared rocks as well as the hematite-enriched porphyry, it is concluded that the shearing must have occurred prior to the hydrothermal event. Thus, the onset of Grenville tectonism in the Killarney region began before 1100 Ma. Sufficient paleomagnetic evidence was not obtained to determine the timing of pre-Grenville tectonism.
Title: A Paleomagnetic Analysis of the Deformation and Hydrothermal Alteration in the Killarney Igneous Complex, Ontario, Author: Andrew Wiacek, Location: Thode